Synthetic CT for single-fraction neoadjuvant partial breast irradiation on an MRI-linac. (16th April 2021) - Groot Koerkamp, M L; de Hond, Y J M; Maspero, M; Kontaxis, C; Mandija, S; Vasmel, J E; Charaghvandi, R K; Philippens, M E P; van Asselen, B; van den Bongard, H J G D; Hackett, S S; Houweling, A C
Abstract: A synthetic computed tomography (sCT) is required for daily plan optimization on an MRI-linac. Yet, only limited information is available on the accuracy of dose calculations on sCT for breast radiotherapy. This work aimed to (1) evaluate dosimetric accuracy of treatment plans for single-fraction neoadjuvant partial breast irradiation (PBI) on a 1.5 T MRI-linac calculated on a) bulk-density sCT mimicking the current MRI-linac workflow and b) deep learning-generated sCT, and (2) investigate the number of bulk-density levels required. For ten breast cancer patients we created three bulk-density sCTs of increasing complexity from the planning-CT, using bulk-density for: (1) body, lungs, and GTV (sCTBD1 ); (2) volumes for sCTBD1 plus chest wall and ipsilateral breast (sCTBD2 ); (3) volumes for sCTBD2 plus ribs (sCTBD3 ); and a deep learning-generated sCT (sCTDL ) from a 1.5 T MRI in supine position. Single-fraction neoadjuvant PBI treatment plans for a 1.5 T MRI-linac were optimized on each sCT and recalculated on the planning-CT. Image evaluation was performed by assessing mean absolute error (MAE) and mean error (ME) in Hounsfield Units (HU) between the sCTs and the planning-CT. Dosimetric evaluation was performed by assessing dose differences, gamma pass rates, and dose-volume histogram (DVH) differences. The following results were obtained (median across patients for sCTBD1 /sCTBD2 /sCTBD3 /sCTDL respectively): MAE inside the body contour was 106/104/104/75 HU and ME was 8/9/6/28 HU, mean dose difference in the PTVGTV was 0.15/0.00/0.00/−0.07 Gy, median gamma pass rate (2%/2 mm, 10% dose threshold) was 98.9/98.9/98.7/99.4%, and differences in DVH parameters were well below 2% for all structures except for the skin in the sCTDL . Accurate dose calculations for single-fraction neoadjuvant PBI on an MRI-linac could be performed on both bulk-density and deep learning sCT, facilitating further implementation of MRI-guided radiotherapy for breast cancer. Balancing simplicity and accuracy, sCTBD2 showed the optimal number of bulk-density levels for a bulk-density approach.